Att öppna upp sitt hem för ensamkommande ungdomar : En studie om ideella familjehem, deras motiv och engagemang - Karlsson,Rebecka (2019)
Opening up your home to unaccompanied young refugees : A study about voluntary foster parents, their motives and commitment Migration politics in Sweden has shifted to a more restrictive stance in the past few years. Unaccompanied asylum-seeking minors are an especially vulnerable group that has been affected by this. Many of them find themselves in a difficult position when they turn 18, when the care and accommodation provided by the Social Services ceases. This started a civic move¬ment of people opening up their homes to unaccompanied young refugees. The aim of this study was to understand the reasons why people choose to commit themselves to help unaccompanied young refugees by offering them housing. This study also investigated how the shift in migration politics has affected the commitment of voluntary foster parents. This is a qualitative study which uses eight interviews with people who have accommodated unaccompanied young refugees and who also signed a petition to stop deporta¬tions. Results show that they motivated their actions by appealing to humanism, personal responsibility and relational ties. Their motives were also closely connected to a sense of disappointment at Swedish authorities failure to provide care and protection to unaccom¬panied minors past 18. This study concludes that these people acted as a reaction to migration policy.
Keywords: unaccompanied minors; voluntary foster care; civic engagement; moral motivation